Developing a spatial measure of exposure to socio-economic inequality in South Africa. Issue 2 (3rd May 2016) - McLennan, David; Noble, Michael; Wright, Gemma
Abstract : It is well documented that South Africa has high levels of poverty, deprivation and income inequality and, additionally, high levels of violent crime and social unrest. Debates about the drivers of social problems such as violent crime have shifted internationally and locally from a focus on poverty to a focus on inequality. However, there is very little empirical evidence to quantify this relationship in South Africa due, in part, to a lack of suitable measures of socio-economic inequality and, in particular, spatial measures of inequality at a detailed geographical level. In the international literature, measures of small area-level spatial inequality have generally been expressed in terms of residential segregation. We use Massey and Denton's five dimensions of residential segregation as our starting point, and assess their appropriateness as measures of spatial socio-economic inequality for the South African context. Focusing on their dimensions of 'exposure' and 'clustering', we develop a measure of spatial inequality which, we argue, can be described as a geographical measure of the 'lived experience of inequality' in that it reflects people's likely exposure to inequality as they go about their daily lives. Our final measure takes the form of a deprivation-adjusted local distance-weighted exposure index.